2011
DOI: 10.1071/hc11023
|View full text |Cite
|
Sign up to set email alerts
|

Rural nurse to nurse practitioner: an ad hoc process

Abstract: INTRODUCTION: Despite a 10-year history of nurse practitioner (NP) development in New Zealand (NZ) there is no formalised or universal process for ensuring the transition of willing nurses to NP status. This unmet need is of particular interest in the rural context where workforce issues are paramount. The aim of this study was to explore the transition from rural nurse to NP in NZ. METHOD: A qualitative descriptive survey was sent to all NZ nurses with a rural address. Ninety-two questionnaires were returned,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Findings from this study have shown the journey from RN to NP employment in rural areas remains an ad hoc process 23 with enormous variability across service providers and locations. Th is analysis also reveals that RNs undertaking the journey are invariably responding to visible unmet need in their communities and that they invest considerable time and eff ort in the process.…”
Section: Discussionmentioning
confidence: 93%
“…Findings from this study have shown the journey from RN to NP employment in rural areas remains an ad hoc process 23 with enormous variability across service providers and locations. Th is analysis also reveals that RNs undertaking the journey are invariably responding to visible unmet need in their communities and that they invest considerable time and eff ort in the process.…”
Section: Discussionmentioning
confidence: 93%
“…Clinical and operational support at all levels is required to ensure efficient day‐to‐day practice. Valuing nurse practitioner clinical expertise and demonstrating a willingness to approve and sanction policies to support practice to full scope is essential (Carryer et al, ; Lloyd‐Jones, ). The key supports identified in this study are funding and a coordinated strategic approach to implementing nurse practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…We screened 18257 records and considered 283 full texts for inclusion in this integrative review. Fifty-six papers met the inclusion criteria (20,21,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)22,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)23,(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)24,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)25,(70)(71)(72)(73)(74)…”
Section: Characteristic Of the Included Studiesmentioning
confidence: 99%
“…Studies were conducted across thirteen countries: nine studies in Oceania (26,32,35,44,60,66,(68)(69)(70), one in Asia ( 36), twenty-one in Europe (20,21,(51)(52)(53)(54)57,58,62,65,67,73,22,74,29,33,34,(41)(42)(43)46), twenty-four in North America (23,24,40,45,(47)(48)(49)(50)55,56,59,61,25,64,71,72,75,27,28,30,…”
Section: Characteristic Of the Included Studiesmentioning
confidence: 99%